Analisis Sistem Antrian Model Multiple Channel-Single Phase untuk Mengoptimalkan Efektivitas Pelayanan Teller Bank - Ulfania Liputo; Muhammad Rifai Katili; Djihad Wungguli (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Queues are commonly encountered in various activities or operations, particularly when available services cannot meet the existing demand. This study aims to analyze the queue system for teller services at Bank Syariah Indonesia (BSI) Gorontalo Branch. The research adopts a quantitative approach, applying the queuing method using the Multiple Channel-Single Phase model. Data analysis was conducted using the